The Clinician Affective Reactivity Index: Validity and Reliability of a Clinician-Rated Assessment of Irritability - Haller, Simone P. (Behav Ther, 2019)
Irritability is impairing in youth and is the core feature of disruptive mood dysregulation disorder (DMDD). Currently, there are no established clinician-rated instruments to assess irritability in pediatric research and clinical settings. Clinician-rated measures ensure consistency of assessment across patients and are important specifically for treatment research. Here, we present data on the psychometric properties of the Clinician Affective Reactivity Index (CL-ARI), the first semistructured interview focused on pediatric irritability. The CL-ARI was administered to a transdiagnostic sample of 98 youth (M age = 12.66, SD = 2.47; 41% female). With respect to convergent validity, CL-ARI scores were (a) significantly higher for youth with DMDD than for any other diagnostic group, and (b) showed uniquely strong associations with other clinician-, parent-, and youth-report measures of irritability compared to measures of related constructs, such as anxiety. The three subscales of the CL-ARI (temper outbursts, irritable mood, impairment) showed excellent internal consistency. Test-retest reliability of the CL-ARI was adequate. These data support that irritability can be feasibly, validly, and reliably assessed by clinicians using the CL-ARI. A validated, gold-standard assessment of pediatric irritability is critical in advancing research and treatment efforts.